Proceedings of the 12th Asian Logic Conference Wellington, New Zealand, 15-20 December 2011 - Downey, R. G. (Rod G.); Brendle, Jörg; Goldblatt, Robert; Kim, Byunghan, 1963- (World Scientific, 2013)
The Asian Logic Conference is the most significant logic meeting outside of North America and Europe, and this volume represents work presented at, and arising from the 12th meeting. It collects a number of interesting papers from experts in the field. It covers many areas of logic--